2013
DOI: 10.1016/j.cmet.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of LY2405319, an FGF21 Analog, in Obese Human Subjects with Type 2 Diabetes

Abstract: Fibroblast growth factor 21 (FGF21) is a recently discovered metabolic regulator. Exogenous FGF21 produces beneficial metabolic effects in animal models; however, the translation of these observations to humans has not been tested. Here, we studied the effects of LY2405319 (LY), a variant of FGF21, in a randomized, placebo-controlled, double-blind proof-of-concept trial in patients with obesity and type 2 diabetes. Patients received placebo or 3, 10, or 20 mg of LY daily for 28 days. LY treatment produced sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
706
9
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(798 citation statements)
references
References 40 publications
(68 reference statements)
45
706
9
5
Order By: Relevance
“…Treatment with FGF21 conferred beneficial effects on body weight, glucose, and lipid metabolism in animal studies,2 and similar benefits were demonstrated in humans treated with FGF21 analogues 3, 4. On the other hand, raised FGF21 levels have been found in various cardiometabolic conditions in clinical studies, suggesting a reactive change to FGF21 resistance or the underlying metabolic disturbances 1.…”
Section: Introductionmentioning
confidence: 75%
“…Treatment with FGF21 conferred beneficial effects on body weight, glucose, and lipid metabolism in animal studies,2 and similar benefits were demonstrated in humans treated with FGF21 analogues 3, 4. On the other hand, raised FGF21 levels have been found in various cardiometabolic conditions in clinical studies, suggesting a reactive change to FGF21 resistance or the underlying metabolic disturbances 1.…”
Section: Introductionmentioning
confidence: 75%
“…Together, these studies show that dietary interventions stimulate the growth of beneficial gut bacteria, which may in part contribute to reverse NAFLD and hepatic insulin resistance. Could be considered as a treatment for NAFLD, but requires further investigations in humans Gaich et al, 2013, Huang et al, 2013 Low-fat or low-carbohydrate lowcalorie diet…”
Section: Treatment Of Mets and Nafldmentioning
confidence: 99%
“…This increase in FGF21 plasma levels may reflect a state of FGF21 resistance. Nevertheless, FGF21 action was investigated in obese human subjects with type 2 diabetes by the use of an analog, LY2405319 (Gaich et al, 2013). In this clinical trial, the FGF21 analog produced significant improvements in dyslipidemia, body weight and fasting plasma insulin decreased, but only at higher concentrations of the analog.…”
Section: Treatment Of Mets and Nafldmentioning
confidence: 99%
“…Therefore, it is important not only to acutely activate thermogenesis in brown adipocytes but also to increase their number and their capacity for thermogenesis [64]. Among the approaches being investigated are mimetics of irisin and fibroblast growth factor-21 [65,66], though recent work casts doubt on the role of irisin because many studies have used commercial ELISA kits to detect irisin that cross-react with other proteins [67].…”
Section: Brown Adipose Tissuementioning
confidence: 99%